A systematic review on factors influencing mobile phone addiction among youths in Asean countries - Ahmad Ghazali, Akmar Hayati; Bolong, Jusang; Abu Samah, Asnarulkhadi; Fadzil, Mohd Fauzi (Human Resource Management Academic Research Society, 2019)
Mobile phone addiction has become one of the main issues today affecting youths in ASEAN countries. There have been limited systematic reviews than most on the social perspective of mobile phone addiction among youths, thus the lack of related articles call for a focus on systematic review related to mobile phone addiction among youths in ASEAN countries. This systematic review is guided by PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) as it offers current state of understanding on a topic. Based on the systematic review on Scopus, seven related studies were chosen. Three main themes of mobile phone addiction among youths were identified, namely: communication, visible design, entertainment and leisure. From the three main themes, nine sub-themes have emerged. Future studies are recommended to place their focus on qualitative study, extend studies in Brunei, Cambodia, Indonesia, Laos, and Myanmar. In the future, studies should focus on determining the statistics of mobile phone addiction among youths in ASEAN countries.